Identifying Macroeconomic Factors that Affect the Share Prices of JSE-Listed Firms - Robbetze, Natasha; Niet, Beitske Van der (International Journal of Economics and Financial Issues, 2025)
This research was undertaken to investigate the effect of macroeconomic indicators on the share prices of the top 40 JSE-listed firms. This study employed a mixed exploratory design and used secondary data. A mixed-method approach was followed by applying a systematic review and an empirical analysis. The findings of this paper demonstrated that strong, positive correlations exist between share prices and macroeconomic factors. CPI, exchange rates, GDP and money supply were strongly correlated with share prices. It was also found that identical correlations exist between share prices, CPI, GDP and money supply. This indicates that CPI, GDP and money supply reflect similar aspect of economic activity. The application of multiple regression analysis demonstrated that 97.1% of changes in share price of the sampled firms can be estimated through the modelling of CPI, exchange rates and repo rates. In conclusion, it is posited that macroeconomic factors affect the share price of the top 40 JSE-listed firms and that such an effect cannot be avoided by the firm.